A crystallographic study of the structure of some antibiotics - Diamand, R (1963)
The crystal structure of 6-aminopenicillanic acid (C8, H12, N2, O3, S) (I) and cephalosporin Cc (C14, H17, O6, N3, S; CH3CO2H), (II) have been determined by X-ray crystallographic analysis. 6-aminopenicillanic acid crystallises in flat orthorhombic plates, Crystal data. a = 6.24 ± .02 Å, b = 14.83 ± .04 Å, c = 10.49 ± .03Å space group P212121 Z=4. Using copper Kα radiation layers okl - 4kl and hkO to hk8 were recorded on equi-inclination Wissenberg photographs. A total of 988 reflections were measured visually out of a possible 1170 in the copper sphere. A Patterson function was calculated using data sharpened by the finction 1⁄f2 exp.(3 Sin2θ), where f was the scattering factor for carbon; from this a superposition function was calculated. It was possible to obtain all atomic positions from this. These were refined using anistropic and isotropic least squares procedures, the final positions have calculated deviations of about .01Å. The final agreement factor was 11.6% using isotropic and 9.7%, anistropic temperature factors. The structure is similar to that reported by Crowfoot, Bunn, Rogers-Low and Turner-Jones for potassium benzyl penicillin except that in the thiazolidine ring the atom out of the plane of the other four is the nitrogen instead of the carbon to which the carboxyl group is attached, as in the other penicillins. The bond between the sulphur and the gem-dimethyl group is longer in all the penicillins than the generally accepted value for a C - S single bond (1.86 Å compared with 1.81 - 1.82 Å). The length of the C - N bond in the β-lactam group falls between that of a C - N single bond and that of an ordinary C - N peptide bond; this is probably caused by the lack of resonance in the fused β-lactam ring. Cephalosporin Cc crystalises in flat orthorhombic needles (a = 5.04 ± .0 Å, b = 7.00 ± .02 Å, c = 54.6 ± .2 Å), space group P212121. 1521 Reflections out of a possible 2580 in the copper sphere were measured visually on equi-inclination Wissenberg films (layers okl - 3kl and hol - h51). The structure was determined and refined in a similar fashion to 6-aminopenicillanic acid, though because of the larger size of the molecule three rounds of Fourier refinement were needed before it was possible to use the least square procedure. The final agreement after eight rounds of least squares refinement was 10.6%, with calculated standard deviations of about .01 Å. The structure was identical to that proposed by Abraham and Newton. The bond distances were all within the expected range of values. The α-amino group of the side chain together with the acetic acid of crystallisation formed a hydrogen bond system around the screw axis parallel to b. There was no significant difference between the lengths bonds of the β-lactam group in cephalosporin Cc and in 6-aminopenicillanic acid. [For the diagrams to accompany this abstract, please consult the PDF.]